2019
DOI: 10.1186/s12610-019-0096-4
|View full text |Cite
|
Sign up to set email alerts
|

Colibri® insecticide induces male reproductive toxicity: alleviating effects of Lannea acida (Anacardiaceae) in rats

Abstract: Background: Imidacloprid, a neonicotinoid insecticide, has been associated to severe reproductive toxicity in mammals. Although some preventive measures have been reported, curative strategies are yet to be explored. The present study was designed to investigate the alleviating effects of Lannea acida on the reproductive toxicity of colibri®, a commercial formulation of imidacloprid, in adult male rats. Materials and methods: Seventy rats were orally administered with colibri® (22.5 mg/kg, 10 mL/kg) for 14 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 40 publications
6
14
0
Order By: Relevance
“…The weight of the epididymis did not differ significantly between groups, but in accordance with the results for the animal weight gain, the absolute weight of the testis was significantly lower in rats treated with the highest dose of imidacloprid compared to the negative control group and rats treated with the lowest dose of imidacloprid. Sub-chronic exposure of adult male Wistar rats to the ten-times higher dose (22.5 mg/kg b. w./day) also resulted in a significant decrease in weight gain, decrease in the relative and absolute weight of the testis, and relative weight of the epididymis compared to the controls [ 14 , 25 ]. The authors stated that the lower testicular and epididymal weight is a direct consequence of the decrease in plasma testosterone and total protein content, considering that these organs require a continuous androgenic stimulation for their normal growth and functions [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The weight of the epididymis did not differ significantly between groups, but in accordance with the results for the animal weight gain, the absolute weight of the testis was significantly lower in rats treated with the highest dose of imidacloprid compared to the negative control group and rats treated with the lowest dose of imidacloprid. Sub-chronic exposure of adult male Wistar rats to the ten-times higher dose (22.5 mg/kg b. w./day) also resulted in a significant decrease in weight gain, decrease in the relative and absolute weight of the testis, and relative weight of the epididymis compared to the controls [ 14 , 25 ]. The authors stated that the lower testicular and epididymal weight is a direct consequence of the decrease in plasma testosterone and total protein content, considering that these organs require a continuous androgenic stimulation for their normal growth and functions [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the activity of antioxidant enzymes indicates that exposure to imidacloprid caused moderate toxicity in the epididymis, while the absence of the effect of imidacloprid on the measured parameters in the testis can be attributed to the very low doses applied in this study. A recent study by Tetsatsi et al [ 25 ] reported a significant increase in the activity of antioxidant enzymes SOD, CAT, and total peroxidases in the testes of adult male rats after 14 days of treatment with a commercial formulation of imidacloprid (Colibri ® ) at a dose of 22.5 mg/kg b. w./day. However, results of several other studies reported a decrease in the concentration of GSH and the activity of antioxidant enzymes (CAT, SOD, GPx and GST) in the testes of rats exposed to different doses of imidacloprid [ 6 , 7 , 12 , 14 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colibri® (Sun Valley Hall Limited-Hong Kong), a commercial formulation of IMI (30 g/l), is a widely used insecticide because of its broad spectrum of action. One liter of this compound (Bach N° SVH161104) was purchased from the Dschang market and the working solution prepared in distilled water as described by [19] . Assay kits for estradiol, progesterone, LH and FSH (TAIWAN Mouse/Rat ELISA) were used according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, IMI has also been demonstrated be very toxic in human prostate epithelial cells and able to induce apoptotic effects as well as oxidative stress [122]. In in vivo study, the IMI exposure has been demonstrated to induce weight changes in absolute and relative prostate weights such that it could always be associated with a decrease in T [123,124]. Therefore, IMI has been shown to be associated with EDs [105].…”
Section: Pesticides/biocides and Plasticizersmentioning
confidence: 99%